2015
DOI: 10.1126/scitranslmed.aaa5597
|View full text |Cite
|
Sign up to set email alerts
|

A screen of approved drugs and molecular probes identifies therapeutics with anti–Ebola virus activity

Abstract: Currently, no approved therapeutics exist to treat or prevent infections induced by Ebola viruses, and recent events have demonstrated an urgent need for rapid discovery of new treatments. Repurposing approved drugs for emerging infections remains a critical resource for potential antiviral therapies. We tested ~2600 approved drugs and molecular probes in an in vitro infection assay using the type species, Zaire ebolavirus. Selective antiviral activity was found for 80 U.S. Food and Drug Administration–approve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
295
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(304 citation statements)
references
References 56 publications
(112 reference statements)
6
295
1
1
Order By: Relevance
“…This dataset overlaps to some extent with another review that identified over 60 molecules 15 . Two recent repurposing screens identified 53 16 and 80 17 compounds with antiviral activity which also overlap the earlier screens. Additional studies have identified small number of inhibitors 18, 19 .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…This dataset overlaps to some extent with another review that identified over 60 molecules 15 . Two recent repurposing screens identified 53 16 and 80 17 compounds with antiviral activity which also overlap the earlier screens. Additional studies have identified small number of inhibitors 18, 19 .…”
Section: Introductionmentioning
confidence: 68%
“…Such an approach may be a useful way to leverage the HTS data that has already been developed at great cost. In this study we have focused on just the data from a single group 3, 31 but it may also be possible to combine this with the data from the other high throughput screens 2, 16, 17 to provide a much larger training set. There is also the opportunity to apply many different computational approaches beyond those described here to identify whole cell active compounds against EBOV.…”
Section: Discussionmentioning
confidence: 99%
“…Small-molecule drugs, like bepridil or sertraline, may cause side effects since they show cytotoxicity to cultured cells (18). Furthermore, to date, no drug candidate has been designed to block EBOV sexual transmission, which is a novel EBOV transmission pathway (10).…”
Section: Discussionmentioning
confidence: 99%
“…***, P Ͻ 0.001. which block viral entry by targeting two different sites on the Zaire GP (30,31). Then, we tested two small-molecule compounds, bepridil and sertraline, which have been considered inhibitors of EBOV function before or at the fusion step (18). As shown in Table 3, HP-HSA exhibited more potent Zaire PsV entry-inhibitory activity (lower EC 50 s and EC 90 s) than any of the drug candidates noted above.…”
Section: Fig 3 Ex Vivomentioning
confidence: 99%
See 1 more Smart Citation